Carta de José Celso Barbosa a Roberto H. Todd - Todd, Roberto H.; Celso Barbosa, José (My University, 1921)
(1)Candidatos para gobernador (2)Vacantes para la corte suprema
Keywords: Political candidates--Puerto Rico.; Conrado Hernández, José, 1849–1932; Candidatos políticos--Puerto Rico.; Rossy y Calderón, Manuel F., 1861-1932; Sopris, William; Coll y Cuchí, Cayetano, 1881-1961